Rural economy of India / by N. L. Murthy and K. V. Narayana - "Murthy, N. L." (Delhi, 1989)
This book comprises of eighteen research papers in which the various facets of Indian rural economy have been critically examined. Some of the papers analyse the impact of rural development programmes on intended target groups introduced from time-to-time. Some of the important facets covered in the volume include land reforms, pro blems of the rural labour, rural credit, modernisation of agriculture, agricul tural marketing, panchayat raj, rural artisans, social forestry and the tribal problems. On the whole, the papers seek to emphasise that there is a lot to be done in future than what has been in the past and our future effort should be fundamentally aimed at re structuring the land relations in rural areas to achieve the desired results.
Keywords: Rural development-India